Genesis of subtropical soils with stony horizons in NE Argentina: Autochthony and polygenesis - Morras, Hector; Moretti, Lucas Martin; Piccolo, Gabriel Agustin; Zech, Wolfgang H. (Elsevier, 2019)
Deep red soils, combining characteristics of highly weathered materials together with a significant degree of clay illuviation and with stony horizons close to the saprolite, are found in the Province of Misiones, northeastern Argentina. Two basic types of stony horizons have been found, which with the fine-grained material above are together considered autochthonous. The first one is a “ferruginous nodular horizon”, composed mainly of in situ goethitic nodules of gravel size resulting from weathering and glaebulization processes of basalt. The second are “siliceous horizons” which are also in situ, derived from pre-existing quartz veins within the basalt. In contrast, different analytical evidences, particularly the vertical and geographical variations in the SOM-stable carbon isotope ratios and the mineralogical composition of fine and coarse fractions, suggest that these red subtropical soils are polygenetic, being the result of a two-fold process linked to paleoecological fluctuations. In the framework of these results, different interpretations about the origin of these soils and their parent materials, and particularly the “tropical loess” theory, are discussed.